Efektivitas Pelaksanaan Program Bantuan Sosial Tunai (Bst) Periode Oktober-Desember 2020 Bagi Masyarakat Terkena Dampak Covid-19 Di Kelurahan Padang Bulan Selayang Ii Kota Medan - Ronaldo Napitupulu; Fajar Utama Ritonga (Jurnal Ilmiah Wahana Pendidikan, 2023)
Padang Bulan Selayang II Village is one of the ward that organizes the distribution of Cash Social Assistance (BST) activities. Cash Social Assistance (BST) with the target of Beneficiary Families (KPM) who meet the requirements in the village. Cash Social Assistance (BST) is distributed by transfer to the account of each recipient in the amount of IDR 300,000/month for one family head. During the implementation of the Cash Social Assistance (BST) there were still some residents of Padang Bulan Selayang II Village, Medan City, who did not comply with health protocols such as not keeping their distance, wearing masks. Some people sometimes don't care about things like that, so the kelurahan as the organizer of the distribution is in accordance with the Decree of the Minister of Social Affairs Number 54/HUK/2020 regarding the implementation of Cash Social Assistance in handling COVID-19 that the organizers carry out socialization of BST activities according to the region. Then, then, the data held by both the central and regional governments that are used as target data for social assistance recipients have the potential to not be right on target. The researcher uses Sutrisno's theory of program effectiveness which consists of (a) understanding the program, (b) right on target (c) on time (d) achieving goals (e) real change. This study uses a descriptive research method with a qualitative approach. Data was collected by observation, interviews and documentation. The results showed that of the five indicators there were three indicators that were not yet effective and two indicators that answered the research problem, namely (a) understanding of the program, in this indicator the socialization provided by the kelurahan to the community during the implementation of BST for the October-December 2020 period was not yet effective. Because there was no special socialization given to the public regarding the BST program and health protocols, so that the public only knew the nominal amount of BST, which was Rp. 300,000 per month, and the delivery of the health protocol was carried out while giving the BST recipient letter to the community. (b) right on target, on this indicator, the data collection process carried out by the kelurahan during the implementation of the BST for the October-December 2020 period has not been effective and the kelurahan admits that it does not re-data beneficiary families (KPM) with the kelurahan party providing data on community residents Padang Bulan Selayang II to the social service, which was later inaugurated by the social service, did not re-register the KPM which resulted in the uneven distribution of BST in the Padang Bulan Selayang II Village, Medan City.